Free vibration of thin-walled composite beams with static initial stresses and deformations - Machado, Sebastián Pablo (2007)
The influence of the initial in-plane deformations, generated by the action of a static external loading, as well as the effect of shear flexibility on the dynamic behavior of bisymmetric thin-walled composite beams has been investigated in this paper. The analysis is based on a geometrically non-linear theory based on large displacements and rotations. The Ritz variational method is used in order to discretize the governing equation and an analytical method is used to obtain the natural frequencies. In the investigation open cross-section beams subjected to initial uniform moment, distributed load and concentrated load are considered. The numerical results show that when the ratio of the smaller axis flexural stiffness to the major axis flexural stiffness is large, classic analysis of vibration may lead to inaccurate predictions because of the effects of initial displacements. Besides, the effects of span length and height of the load point have also been investigated for different laminate stacking sequences.